MERDEKA CURRICULUM: IMPLEMENTATION OF LEARNING AND ASSESSMENT AT SMA NEGERI 10 PONTIANAK - Amallia Putri (Sean Institute, 2023)
This research aims to determine the learning implementation system and independent curriculum assessment at SMA Negeri 10 Pontianak. The initial problem finding of this research was that there were some students who stated that there were no visible changes in their learning outcomes after implementing the independent curriculum at SMA Negeri 10 Pontianak. In order to obtain certainty from the statements made by some students at SMA Negeri 10 Pontianak, the researchers conducted more in-depth research regarding the implementation of learning and assessment of the independent curriculum at the SMAN. Thus, a descriptive qualitative research method was chosen to describe the implementation of the independent curriculum at SMA Negeri 10 Pontianak. Data collection uses observation techniques, interviews and documentation studies. The research population is teachers and students of SMA Negeri 10 Pontianak. The research sample was the deputy principal and several students taken randomly. The research results were analyzed using analysis according to Milles and Huberman. The results of the research show that the implementation of the independent curriculum in the learning process by teachers at SMA Negeri 10 Pontianak is still in the process of adaptation and often faces problems for which solutions are sought together. Most teachers actively participate in activities such as training, webinars and workshops and the like, which are held both at school and outside school. The problems that teachers at SMA Negeri 20 still face are the challenges of human resources (teachers), the ability of teachers to empower digital-based technology facilities, challenges in strengthening communication networks and partnerships between educational units and related stakeholders. Meanwhile, in the assessment system at SMA Negeri 10 Pontianak, teachers increasingly have the freedom to determine the type, form and time of implementation based on the characteristics of the learning objectives.